Evaluación para la admisión a la universidad - Torreblanca Villavicencio, Alberto (2013)
The Admissions and Information Office of the Pontifical Catholic University of Perú, through its Evaluation Section, is responsible forthe design and application of tests that must be given by any applicant who wants to follow higher education. This article describes the process of developing these testing tools, and introduces a general reflection –based on gained experience– about the new challenges we face in the field of evaluation of skills in higher education.